(untitled) (Balthazar, 2021)
Testimonies of Vittoria Levi in Veniselli, of Lea and Rachele Levi, born in Rhodes and deported to Auschwitz, Willistadt, Theresienstadt, and of Mrs Montuoro deported to Ravensbrück.